Alphabet ‘N’ Beginning Group of Similar Letters in English Words and Their Dissimilar Pronunciations - Koli, Uttam Balu (Journal of Advanced Research in English & Education, 2022)
The present research article mentions the alphabet ‘N’ beginning group of similar letters in different English words having dissimilar pronunciations. The alphabet ‘N’ beginning group of similar letters in different English words, having dissimilar pronunciations, are forty-two in numbers which are: na, nae, nce, nco, nd, nde, ndi, ndo, ndu, ne, nee, nei, neo, nfe, nfi, nge, ngi, ngre, ni, nne, nni, nno, nnu, no, nou, now, ns, nscie, nse, nsi, nso, nspi, nsta, nsu, nta, nte, ntia, nto, ntra, ntro, nu and ny. The select alphabet of ‘N’ beginning group of similar letters in different English words, having dissimilar pronunciations, have been put forth with three hundred and forty-six examples including words and their phonetic transcriptions which will surely support the learners of English language to find the excellence in the select piece of work. The importance and limitations of the study, hypothesis, objective, research methodology, sources of data collection and findings have been given. The present research article closes with the conclusion and the reference list. How to cite this article: Koli UB. Alphabet ‘N’ Beginning Group of Similar Letters in English Words and Their Dissimilar Pronunciations. J Adv Res Eng & Edu 2021; 6(3): 6-16. DOI: https://doi.org/10.24321/2456.4370.202108